Operational properties of catalysts for non-extractive oxidative demercaptanization of oil and petroleum fractions - Yu. A. Gavrilo; I. V. Pletneva; E. N. Silkina (Тонкие химические технологии, 2015)
The results of identification of the main operational properties of metallocomplex catalysts solutions for non-extractive oxidative sweetening of natural hydrocarbons and their products are provided in this article. These catalysts allow carrying out the catalytic oxidation of hydrogen sulfide and mercaptans in hydrocarbon media directly. This method allows to exclude from the technological cycle the need to use large volumes of extracting agents (aqueous alkaline solutions), which greatly simplifies the purification technology and eliminates the stage of recycling sulfuralkaline waste. These catalysts are oxidizing systems, which can have a negative impact on their storage and use. Therefore, it was necessary to determine the influence of the synthesis conditions and the composition of the catalyst solution on viscosity, pour point, surface tension and corrosion properties. The impact of storage duration and its conditions on the catalysts activity in the oxidation of H2S and light mercaptans in oil and oil products was studied. The results showed that the catalytic systems based on copper salts and amino alcohols correspond to the requirements for industrial applications.